Does remittance inflow stimulate electricity consumption in India? An empirical insight. (22nd October 2020) - Sahoo, Malayaranjan; Sethi, Narayan
Abstract : Purpose: The purpose of this paper is to examine whether remittance inflow stimulate electricity consumption in India with other macroeconomic variables such as FDI, trade openness and urbanization in energy demand function from 1975–2017. Design/methodology/approach: We have applied structural break and co-integration tests for stationarity and long-run relationship between the variables. The Toda–Yamamatoo causality is employed for investigation of causal relationship between the variables, and robustness of causality linkages is also tested by applying innovative accounting approach (IAA). Findings: Our empirical analysis shows there is presence of long-run relationship among the variables. We find that remittance inflows stimulate electricity consumption in India. Industrialization is positively linked with electricity demand. However, trade openness declines the electricity consumption, but urbanization increases it. Furthermore, remittances inflows cause electricity consumption. Originality/value: On the basis of findings, we conclude that due to positive impacts of remittances inflows, trade openness and urbanization, policymakers in the Indian economy need to be careful while designing sustainable environment policy. Otherwise, any sustainable environment policy in the name of protecting green environment will hamper the growth of remittance inflows, urbanization and FDI. If this exists, it may be argued that sustainable growth in India will not be possible in the face of sustainable environment policy.